Contact resistance heating of unidirectional carbon fibre tows in a powder-epoxy towpregging line. (14th September 2022) - Çelik, Murat; Noble, Thomas; Haseeb, Abdul; Maguire, James; Robert, Colin; Ó Brádaigh, Conchúr M.
ABSTRACT: Contact resistances play a major role in Joule heating systems. Identifying contact resistances provides a better understanding of the heating process and increases the accuracy of the process models. In this study, contact resistances of the Joule heating section in a powder-epoxy-based towpregging line were explored. For different process parameters, such as production speed, tension, and temperature, contact resistances occurring between metal roller electrodes and dry carbon fibre tows (i.e. without powder-epoxy) were measured to gain an insight into the heating process. Moreover, the effect of contact resistance heating on the temperature profile of the carbon fibre tows was determined with an infrared thermal camera. A simplified finite element model was developed to calculate the temperature distribution onthe carbon fibre tow, which showed a good agreement with the experimental data. Results suggest that contact resistances in the towpregging line were significant and contact resistance heating changed the heating profile.